2018
DOI: 10.1111/adb.12685
|View full text |Cite
|
Sign up to set email alerts
|

A dual‐process exploration of binge drinking: Evidence through behavioral and electrophysiological findings

Abstract: The dual-process model, describing addictive disorders as resulting from an imbalance between increased automatic approach behaviors towards the substance and reduced abilities to control these behaviors, constitutes a sound theoretical framework to understand alcohol-use disorders. The present study aimed at exploring this imbalance at behavioral and cerebral levels in binge drinking, a pattern of excessive alcohol consumption frequently observed in youth, by assessing both reflective control abilities and au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 46 publications
1
18
0
5
Order By: Relevance
“…In early perceptual components, the scarce findings range from subtle correlations (as in our research) to larger [52,53] or smaller [82] P1 amplitudes. Regarding later cognitive ERP components, larger N2-NoGo amplitudes in response to nonalcohol stimuli (as we observed) may reflect compensatory conflict monitoring processes that overcome bias to an alcohol preponderant context; however, such compensatory mechanisms may be overcome by a longer history of consumption (or more difficult task), as reflected by lower N2-NoGo or poorer behavioural execution reported in other studies [45,49]. The same seems to occur with the P3-NoGo component, as larger amplitudes were reported in a longitudinal research [55] only during the second evaluation.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In early perceptual components, the scarce findings range from subtle correlations (as in our research) to larger [52,53] or smaller [82] P1 amplitudes. Regarding later cognitive ERP components, larger N2-NoGo amplitudes in response to nonalcohol stimuli (as we observed) may reflect compensatory conflict monitoring processes that overcome bias to an alcohol preponderant context; however, such compensatory mechanisms may be overcome by a longer history of consumption (or more difficult task), as reflected by lower N2-NoGo or poorer behavioural execution reported in other studies [45,49]. The same seems to occur with the P3-NoGo component, as larger amplitudes were reported in a longitudinal research [55] only during the second evaluation.…”
Section: Discussionsupporting
confidence: 64%
“…Task design may also explain the absence of N2-NoGo differences in a letter Go/NoGo task with pictures of alcoholic beverages and neutral pictures as a background [48]. The fact that alcohol pictures were not explicitly related to task instructions may have led to the lack of differences, as shown by Lannoy et al [49] in a study in which group differences in N2-NoGo amplitudes and behavioural performance only emerged when Al pictures were explicitly related to the task instructions. Furthermore, in contrast to the compensatory hypothesis, the aforementioned research found smaller N2-NoGo amplitudes for Al pictures in BDs (relative to CNs), suggesting that BDs may experience some difficulties at the attentional level in inhibiting a prepotent response when alcohol pictures are present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two central aspects of methamphetamine use disorder are a characteristic reactivity to drug cues (itself involving attentional bias towards drug cues, their increased salience, and ultimately the induction of craving) 11 , 12 , and failures of executive control and response inhibition 13 . These phenomena widely figure in models of a substance use disorder, such as the “impaired response inhibition and salience attribution” model 14 and dual-process models, which comprise automatic approach behavior towards substances and reduced abilities to inhibit these behaviors 15 . An increasing number of task-based fMRI studies in MUD have investigated the neural correlates of either methamphetamine cue-reactivity, using conventional cue exposure tasks 16 – 19 or cognitive control and response inhibition, using varieties of Stroop, Stop Signal or Go-NoGo tasks 20 22 , but an approach with greater ecological validity has been to assess response inhibition concurrently with cue-reactivity.…”
Section: Introductionmentioning
confidence: 99%